PERAN ORANG TUA DALAM MEMBINA AKHLAK ANAK REMAJA DI DESA LUMBANG KECAMATAN SAMBAS - Mariyanti Mariyanti (Tarbiya Islamica, 2014)
The study was conducted because it saw the phenomenon of the morals of commendable children who were not guided, therefore parents played a role in familiarizing children with commendable character. This research aims to; (1) Describe the planning of the role of parents in fostering children's morals in Lumbang Village, Sambas District in 2020. (2) Describe the supporting and inhibiting factors of parents' efforts to foster children's morals in Lumbang Village, Sambas District in 2020. Sources of data in this study are parents who provide guidance to children and children who receive guidance from parents in Lumbang Village. The approach taken to answer the problem in this research is qualitative, with a descriptive method. To find data related to the focus and objectives of the study, the researcher chose the method of observation, interviews, and documentation. To arrive at the conclusion of the data analysis that researchers used after data collection consisted of: data reduction, data display, verification and conclusion drawing. Meanwhile, to check the validity of the data, continuous observation, data triangulation and member check were used. The results of the study can be concluded, namely: 1) Planning for parental efforts in using habituation methods to foster children's morals in Lumbang Village, Sambas District in 2020 is carried out by giving advice to children to orderly worship five times accompanied by habituation and example from parents. Carry out congregational prayers, dhikr, pray every time you do something, get used to memorizing several prayers in life, habituation of cleanliness by checking children's clothes, nails and bodies, getting used to reading the Qur'an by memorizing short letters to children , giving punishment for breaking the rules or doing something wrong, giving love to children. 2) Factors supporting and inhibiting parents' efforts in using habituation methods to foster children's morals in Lumbang Village, Sambas District in 2020: Supporting factors, namely; good family conditions at home, good environment, high parental attention to children. A quiet and conducive environment. Inhibiting factors are: lack of parental knowledge about Islam, poor social environment, limited time with children, lack of parental attention to children, technological advances that affect children.